Cardiovascular surgery experience does not significantly improve patients' response to stroke. Issue 10 (12th September 2019) - Li, Shengde; Cui, Li‐Ying; Anderson, Craig; Gao, Chunpeng; Yu, Chengdong; Shan, Guangliang; Wang, Longde; Peng, Bin; ,
Abstract: Objectives: Patients with a history of cardiovascular surgery are at risk of stroke, and immediately calling emergency medical services (EMS) after stroke onset is crucial to receiving effective reperfusion therapy. We aimed to determine the effect of a history of cardiovascular surgery on patients' ability to recognize stroke and intent to call EMS. Methods: We performed a cross‐sectional community‐based study from January 2017 to May 2017. A total population of 186, 167 individuals, recruited from 69 administrative areas across China, was analyzed. Different multivariable logistic regression models were performed to identify the associations between cardiovascular surgical history and stroke recognition or intent to call EMS, respectively. Results: 0.1% of the total population had a history of cardiovascular surgery. In the surgery group, the estimated stroke recognition rate (SRR) and correct action rate (CAR) were 84.9% and 74.7%, respectively. The prevalence of cardiovascular risk factors was significantly higher in the surgery group. Cardiovascular surgical history was not associated with recognition of stroke across different models. The surgery group was more likely to call EMS, but the difference was not significant after full adjustment (OR: 1.40, 95% CI: 0.99–1.98, p = .0572). Conclusions: Cardiovascular surgical history does not influence patients' likelihood of calling EMS more often at stroke onset. Patients receiving cardiovascular surgeries should be counseled regarding stroke recognition, proper response to stroke, and the importance of controlling risk factors. Abstract : Only 0.1% of the total population had a history of cardiovascular surgery. However, cardiovascular surgical history does not influence patients' likelihood of calling EMS more often at stroke onset.